Pelaksanaan Operasional Food and Beverage Department dalam Pencapian Excelent Service di Crystal Lotus Hotel Yogyakarta - Desika Murdita Wulansari; Fathurrahman Nurul Hakim (Universitas Bina Sarana Informatika, 2019)
Abstract - The food and beverage department is a part of the hotel that has quite an important task because this department is tasked with served food and beverage needs. Food and beverage department is divided into two parts, Food and beverage products and food and beverage service. The use of service standards that advance guest satisfaction is very important to be applied in food and beverage services which will contribute to increased revenue and can also open new market shares for hotels, there are several factors that can play a role in the implementation of excellent service, inadequate communication, will disrupt the work of the two departments, in addition to the irregular division of work that makes some food and beverage service work is not finished on time which causes discomfort customer. The number of equipment food and beverage services that are not in accordance with the ongoing event also disrupts the smooth operation, this should be avoided by Crystal Lotus Hotel. The research method used is descriptive qualitative and data collection techniques used are observation, interviews, documentation and literature study. The results of this study are in the implementation of operational food and beverage departments in the excellence of excelent service in handling breakfast, lunch and dinner. From the research it can be concluded from the guest comment card that enters the Food and Beverage Department - the average guest says they are satisfied with the service but there are some note that the lack of staff to charge caused sluggish service, lack of equipment resulted in operational disruptions. The solution to overcome the obstacles experienced by the food and beverage department istheaddition of staff and equipment procurement. Keywords: Food and Beverage, Excelent service, operational Abstrak - Food and beverage department merupakan bagiand ari hotel yang memiliki tugas cukup penting karena departemen ini bertugas memenuhi kebutuhan makanan dan minuman. Food and beverage department dibagi menjadi dua bagian yaitu food and beverage product danfood and beverage service.Pengunaan standar pelayanan yang mengaju pada kepuasan tamu amatlah penting di terapkan di pelayanan food and beverage yang mana akan memberikan kontribusi pendapatan yang meningkat juga bisa membuka pangsa pasar baru untuk Hotel, ada bebrapa faktor yang dapat menghabat dalam pelaksanaan pelayanan yang prima yaitu Komunikasi yang kurang baik, akan mengganggu jalannya pekerjaan kedua departemen, selain itu pembagian pekerjaan yang tidak teratur membuat beberapa pekerjaan food and beverage service tidak selesai tepat waktu yang akhirnya menimbulkan ketidak nyamanan pelangan. Jumlah equipment food and beverage service yang tidak sesuai dengan event yang sedang berlangsung juga mengganggu kelancaran operasional, hal ini yang seharusnya di hindari oleh di Crystal Lotus Hotel. Metode penelitian yang digunakan adalah deskriptif kualitatif dan teknik pengambilan data yang digunakan adalah observasi, wawancara, dokumentasi serta studi pustaka. Hasil penelitian ini adalah dalam pelaksanaan operasionalnya food and beverage departement di pencapian excelent service dalam menangani breakfast, lunch dan dinner.dari penelitian dapat diambil kesimpulan dari guest comment card yang masuk ke Food and beverage departement rata–rata tamu mengatakan puas dengan pelayanan namun ada beberapa catatan yaitu kurangnya staff yang incharge menyebabkan lambannya pelayanan, kurangnya peralatan mengakibatkan ketidak lancaran operasional. Solusi untuk menangani kendala yang dialami food and beverage departement adalah Penambahan staff dan pengadaan equipment. Kata kunci: Food and Beverage, Excelent service, operasional